Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1186/1756-3305-7-298
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular persistence of Anaplasma platys, Ehrlichia chaffeensis, and Ehrlichia ewingii DNA in the blood of a dog and two family members

Abstract: BackgroundAnaplasmosis, caused by Anaplasma phagocytophilum and Anaplasma platys, and ehrlichiosis, caused by Ehrlichia chaffeensis, Ehrlichia ewingii, the "Panola Mountain Ehrlichia" and Ehrlichia muris-like pathogens have been identified as emerging tick borne infectious diseases in dogs and human patients. Persistent intravascular infection with these bacteria is well documented in dogs, but is less well documented in human beings.MethodsSerology and PCR targeting multiple microbial genes, followed by DNA s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
61
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(72 citation statements)
references
References 31 publications
4
61
1
2
Order By: Relevance
“…Comparison of clinical and laboratory findings of patients with PCR-positive and -negative results showed no clear differences, possibly related to the length of time between the acute phase of illness and the sampling for molecular analysis, which was usually 1 year. Nevertheless, it is noteworthy that the patients’ samples harbored detectable Ehrlichia DNA 1 year after the acute phase, which was similar to findings in recent reports ( 9 ). Equally, related to the 2 patients evaluated in this study who had a recent history of infection (CR1 and CR2), no major physical or biochemical alterations were observed, suggesting that disease manifestation was mild or that samples were taken during the convalescent phase.…”
supporting
confidence: 90%
“…Comparison of clinical and laboratory findings of patients with PCR-positive and -negative results showed no clear differences, possibly related to the length of time between the acute phase of illness and the sampling for molecular analysis, which was usually 1 year. Nevertheless, it is noteworthy that the patients’ samples harbored detectable Ehrlichia DNA 1 year after the acute phase, which was similar to findings in recent reports ( 9 ). Equally, related to the 2 patients evaluated in this study who had a recent history of infection (CR1 and CR2), no major physical or biochemical alterations were observed, suggesting that disease manifestation was mild or that samples were taken during the convalescent phase.…”
supporting
confidence: 90%
“…Zobba et al reported this bacterium that infects ruminants as being A. platys-like [11]. Indeed, the infectivity of A. platys for ruminant, previously reported only as an agent of infectious cyclic thrombocytopenia in dogs, had already been documented in ovine from Senegal ( [13] and personal data), and in human [34][35][36]. A. platys like A. bovis is not yet cultured species [37] and recently, analyses of 16S, groEL and gltA genes showed that A. bovis is closely related to A. phagocytophilum [38].…”
Section: Discussionmentioning
confidence: 93%
“…hrlichia chaffeensis, an Amblyomma americanum tick-transmitted rickettsial pathogen, is responsible for human monocytic ehrlichiosis (HME) and also causes persistent infections in people and several other vertebrates (1)(2)(3). The white-tailed deer is the reservoir host for E. chaffeensis, while humans, dogs, and other vertebrate hosts, such as coyotes and goats, are regarded as incidental hosts (4)(5)(6)(7).…”
mentioning
confidence: 99%